Матеріали тшинецького культурного кола з поселення Рованці – Гнідавська Гірка на Волині - Бардецький, Андрій Б. (Muzeum Okręgowe w Rzeszowie, 2023)
The article publishes the materials of the Trzciniec cultural circle (TCC) from the excavations of the multi-layered settlement Rovantsi-Hnidavska Hirka in Volyn. Today, this monument is completely built up with numerous violations of monument protection laws and has already been lost to science. The materials were obtained from rescue excavations in 2009–2010, conducted by the author. In the excavations, four TCC objects were discovered: three pits and the remains of a clay oven, the base of which is paved with fragments of pottery. The pottery from the objects has features different from the pottery of the classical horizon of the TCC in Volyn, which is represented, for example, in ash mounds near the town of Netishyn. It is also different from the ceramics of monuments such as Dubno-Dubovets and Tarakaniv-5, which represent the final horizon of the TCC in Volyn. Сomplex of the Hnidavska Hirka reveals features that are late in relation to the classical ones, so it can be considered as intermediate between the classical and final horizons. On the basis of a comparison with the dating of other monuments, consider the dating of the middle of the 15 th –14 th centuries BC the most suitable for our site in Rovantsi. Clay ovens, similar to the one found, have analogues in other TCC settlements, but they are poorly documented in Volyn.
Materials of the Trzciniec cultural circle from the settlement Rovantsi-Hnidavska Hirka in Volyn
Keywords: Bronze Age; Trzciniec cultural circle; Volyn; oven; pottery